An optically transparent flexible metasurface absorber with broadband radar absorption and low infrared emissivity. (23rd February 2023) - Jing, Huihui; Wei, Yiqing; Kang, Jinfeng; Song, Chengwei; Deng, Hao; Duan, Junping; Qu, Zeng; Wang, Jiayun; Zhang, Binzhen
Abstract: The rapid development of surveillance technology has driven the research of multispectral stealth. Demand for infrared and microwave radar compatible stealth is becoming increasingly urgent in military applications. Herein, a versatile metamaterial absorber is designed and fabricated to simultaneously achieve ultra-broadband radar scattering reduction, low infrared emission, and high optical transparency. The designed structure consists of an infrared stealth layer, radar absorption layers, and backing ground. The infrared stealth layer employs specifically indium tin oxide (ITO) square patches, while the radar absorption layers can be obtained by stacking different size ITO patterned films of the same structure with high surface resistances, realizing broadband microwave stealth performance in the 1.98–18.6 GHz frequency range with an incident angle of 45°. The broad radar stealth and low infrared emissivity of 0.283 are consistent with the simulations and calculations. Furthermore, the designed structure exhibits characteristics such as polarization insensitivity, wide incident angles, optical transparency, and flexibility, allowing for a wide range of applications in various environments.